Downregulation of Cdc6 and pre-replication complexes in response to methionine stress in breast cancer cells - Booher, Keith (Landes Bioscience, 2012)
Methionine and homocysteine are metabolites in the transmethylation pathway leading to synthesis of the methyl-donor S-adenosylmethionine (SAM). Most cancer cells stop proliferating during methionine stress conditions, when methionine is replaced in the growth media by its immediate metabolic precursor homocysteine (Met-Hcy+). Non-transformed cells proliferate in Met-Hcy+ media, making the methionine metabolic requirement of cancer cells an attractive target for therapy, yet there is relatively little known about the molecular mechanisms governing the methionine stress response in cancer cells. To study this phenomenon in breast cancer cells, we selected methionine-independent-resistant cell lines derived from MDAMB468 breast cancer cells. Resistant cells grew normally in Met-Hcy+ media, whereas their parental MDAMB468 cells rapidly arrest in the G(1) phase. Remarkably, supplementing Met-Hcy+ growth media with S-adenosylmethionine suppressed the cell proliferation defects, indicating that methionine stress is a consequence of SAM limitation rather than low amino acid concentrations. Accordingly, mTORC1 activity, the primary effector responding to amino acid limitation, remained high. However, we found that levels of the replication factor Cdc6 decreased and pre-replication complexes were destabilized in methionine-stressed MDAMB468 but not resistant cells. Our study characterizes metabolite requirements and cell cycle responses that occur during methionine stress in breast cancer cells and helps explain the metabolic uniqueness of cancer cells.